Decoding the secreted inflammatory response of primary human hepatocytes to hypoxic stress in vitro - Vodovotz, Yoram (Ann Transl Med, 2019)
BACKGROUND: The cellular and molecular response of liver cells to hypoxic stress is not fully understood. We used computational modeling to gain insights into the inflammatory response of primary human hepatocytes (HC) to hypoxic stress in vitro. METHODS: Primary HC from cancer patients were exposed to hypoxia (1% O(2)) or normoxia (21% O(2)) for 1–48 h, and the cell supernatants were assayed for 21 inflammatory mediators. Data were analyzed by Two-Way ANOVA, Dynamic Bayesian Network (DBN) inference, Dynamic Network Analysis (DyNA), and Time-interval Principal Component Analysis (TI-PCA). RESULTS: The chemokines MCP-1/CCL2 and IP-10/CXCL10, along with the cytokines interleukin (IL)-2 and IL-15 were altered significantly over time in hypoxic vs. normoxic HC. DBN inference suggested central, coordinating roles for MCP-1 and IL-8 in regulating a largely conserved inflammatory program in both hypoxic and normoxic HC. DyNA likewise suggested similar network trajectories of decreasing complexity over time in both hypoxic and normoxic HC, though with differential connectivity of MCP-1, IP-10, IL-8, and Eotaxin. TI-PCA pointed to IL-1β as a central characteristic of inflammation in hypoxic HC across all time intervals, along with IL-15 and IL-10, vs. Eotaxin, IL-7, IL-10, IL-15, and IL-17A in normoxic HC. CONCLUSIONS: Thus, diverse human HC appear to respond in a largely conserved fashion to cell culture stress, with distinct characteristics based on the presence or absence of hypoxia.